2014
DOI: 10.1088/0953-2048/27/5/055023
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of stress distribution in Cu-stabilized GdBCO CC tapes during anvil tests for the evaluation of transverse delamination strength

Abstract: Rare-earth-Ba-Cu-O (REBCO) based coated conductors (CCs) are now being used for electric device applications. For coil-based applications such as motors, generators and magnets, the CC tape needs to have robust mechanical strength along both the longitudinal and transverse directions. The CC tape in these coils is subjected to transverse tensile stresses during cool-down and operation, which results in delamination within and between constituent layers. In this study, in order to explain the behaviour observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 27 publications
2
37
0
Order By: Relevance
“…It occurred due to the stress distribution when a relatively smaller size upper anvil than the tape width was used. In this case, the Cu layer was subjected to the maximum stress induced on the CC tape and singularities occurred on the edges of the upper anvil as reported elsewhere [18]. Similar delamination mechanism was also observed at the edge case of the superconducting layer side as shown in Fig.…”
Section: Mechanical Delamination Testingsupporting
confidence: 65%
See 2 more Smart Citations
“…It occurred due to the stress distribution when a relatively smaller size upper anvil than the tape width was used. In this case, the Cu layer was subjected to the maximum stress induced on the CC tape and singularities occurred on the edges of the upper anvil as reported elsewhere [18]. Similar delamination mechanism was also observed at the edge case of the superconducting layer side as shown in Fig.…”
Section: Mechanical Delamination Testingsupporting
confidence: 65%
“…Van der Laan et al showed the effect of slit on the CC tape which adopts metal organic deposition (MOD) on rolling assisted biaxially textured substrate (RABiTS) process [14]. While Dizon et al reported that the SC film experienced most of the transverse stress when edges of the CC tape were included [18]. In our case, the mechanical delamination strength of the CC tape loaded at the edge part of its superconducting layer side ranged from 38 MPa to 122 MPa (open circle symbol) with an average of 90.6 MPa (closed circle symbols).…”
Section: Mechanical Delamination Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that work hardening of the Cu stabilizer might have occurred. In this anvil configuration, stress concentration is greatest on the Cu stabilizer among the CC tape constituent layers [15]. On the other hand, the stress distribution changes and the maximum transverse tensile stress shifted to the superconducting film in the case of wide upper anvil (4 mm x 8 mm) which covers the whole width of the CC tape [15].…”
Section: C Behavior Under Monotonic and Cyclic Transverse Tensile Lmentioning
confidence: 94%
“…This phenomenon has been observed not only the YBCO CC but also the GdBCO CC samples [12]. So far, there are few numerical simulations that could interpret this experimental phenomenon, since the recently published article by Dizon et al [13] in this year. Here, a 3-D numerical simulation by using ANSYS is presented, in which the bonded restraint between the multilayers was conducted, and the solid 186 hexahedral element with 20 nodes was used.…”
Section: ) Delamination Strength Tests Including Electrical Behaviormentioning
confidence: 79%